2020
DOI: 10.15406/htij.2020.08.00236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of passenger airplane transport on blood

Abstract: Objective: We examined the effects of passenger air transport by regular airplanes for air transportation on blood for transfusion. Materials and methods: Irradiated red blood cell (RBC) solutions were transported by regular passenger airplanes which and were static in the cabin during the flight. Blood samples were evaluated visually and biochemically before and after transport. Hemolysis of the transported samples was compared to that of the non-transported ones. The vibration in the airplanes was also meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…37 These results have been corroborated in the only fixedwing airplane study to date from 2020 where Yakushiji et al demonstrated no changes in blood product quality following airplane transport. 38 A subsequent 2021 study by Selleng et al further demonstrated that helicopter transport does not negatively impact both plasma and red blood cell quality for transfusion purposes. 39…”
Section: Effect Of Aeromedical Transport On Blood Product Viabilitymentioning
confidence: 99%
“…37 These results have been corroborated in the only fixedwing airplane study to date from 2020 where Yakushiji et al demonstrated no changes in blood product quality following airplane transport. 38 A subsequent 2021 study by Selleng et al further demonstrated that helicopter transport does not negatively impact both plasma and red blood cell quality for transfusion purposes. 39…”
Section: Effect Of Aeromedical Transport On Blood Product Viabilitymentioning
confidence: 99%
“…27 Additionally, it has been reported that blood transported by commercial aircrafts in a temperature-controlled refrigerator does not get degraded, and the vibration during transport is clearly less than that during transport by automobiles. 28 Furthermore, using LD-based assessments, bullet trains and Jetfoils (high-speed vessel) have also been examined for their feasibility of use in blood transportation. 25,27,28 For the remaining vehicles, our suggestions are made based on previously unpublished LD-based data.…”
Section: Citationmentioning
confidence: 99%
“…28 Furthermore, using LD-based assessments, bullet trains and Jetfoils (high-speed vessel) have also been examined for their feasibility of use in blood transportation. 25,27,28 For the remaining vehicles, our suggestions are made based on previously unpublished LD-based data.…”
Section: Citationmentioning
confidence: 99%
See 1 more Smart Citation